Exploring the Early Neolithic in the Arabian Gulf: A newly discovered 8,400-year-old stone-built architecture on Ghagha Island, United Arab Emirates. - Kevin Lidour; Noura Al Hameli; Rémy Crassard; Fabian D'Silva; Ahmed Al Haj (PLoS ONE, 2025)
The site of GHG0088, with its two successive main phases of occupation, provides crucial data for re-evaluating our understanding of the Early Neolithic period (c. 6600-5400 cal. BCE) in the Arabian Gulf. The initial phase is marked by durable stone-built structures and evidence of domestic activities and funerary practices, presumably reflecting a settled lifestyle. The material culture includes a lithic industry, tools crafted from marine shells, and plaster vessels indicative of early pyrotechnological skills, while the absence of pottery challenges traditional views of Neolithic material assemblages in the Arabian Peninsula. Analysis of faunal remains indicates a subsistence strategy heavily reliant on marine resources, particularly fish, highlighting the exploitation of the neighbouring sea. While there is no evidence of agriculture or animal herding during that period, the rich coastal ecosystems likely ensured food security, reducing the need for residential mobility. The architectural remnants reveal patterns of continuity and adaptation across both phases. A significant layer of accumulated aeolian sand suggests a period of abandonment, potentially linked to the 8.2 ka BP climatic event. The subsequent reoccupation involved the adaptive reuse of the collapsed structures, transforming them into a temporary shelter for fishers, as suggested by numerous stone weights found. Additionally, the presence of shell beads underscores a renewed significance of marine resources during this second phase of occupation and suggests participation in extensive long-distance trade networks. These findings provide valuable new perspectives on the early stages of the Neolithic period in the Arabian Gulf. Comparisons with other contemporary sites offer a foundation for redefining the Early Arabian Neolithic and its timeline in this region.